The Poetics of Essays by Michael Epstein (the Philosophical Aspect of Genre Form) - Захарова, Елизавета (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2022)
In its most general form, Mikhail Epstein is outlined by such a vast circle of spheres as philology, philosophy, cultural studies, literary criticism, or linguistics. Currently, Epstein’s method is classified by researchers as “analytically-oriented”. The purpose of the article is to determine the set of methods of philosophical essayism by Mikhail Epstein, which will be achieved based on the material of the book The Paradoxes of Novelty. Despite the fact that the author’s self-reflection extends over a large number of articles (“Laws of the Free Genre (Essay and Essayism in the Culture of the New Time)”, “On the Soul. Four Essays”, “Essays on Essays”, “God of Details”, etc.), features of the poetics of essayism such as the author’s principle, imagery, and digressions are revealed in a more focused way, i.e. based on the opening book. The book is notable for its freedom of presentation, its being full of aphorisms, and its lengthy philosophical sayings. Essayisation can be considered the leading genre-forming principle of the book, affecting the way of presenting thoughts. The author’s task is to clarify the meaning of tradition in literature, which is associated with the author’s central interest, namely “culture in its borderline situations”. The factor that holds the texts together is the author’s desire to propose a way to solve the “problem situation”: what is criticism and how to look at literature? The plot of the book is built upon the author’s own questions and personal preferences. The task is to analyse what was written earlier and summarise the milestone results of creative activity. The book has a character of a manifest as the first major work of the author. It contains a programme for Epstein’s future activities, which is confirmed by the subsequent addition and reprint of the publication. It is essential that Russian classical literature was chosen as the material.